Rancangan Ulang Sistem Penyaliran Tambang Bawah Tanah pada Front Penambangan Batubara Tunnel THC-01 di CV. Tahiti Coal, Kecamatan Talawi, Kota Sawahlunto - Anita Lisminiyati; Tamrin Kasim (Journals Mining Engineering : Bina Tambang, 2018)
Existing pumps can not work optimally on mining C.11 and C.12 because the inlet value obtained is greater than the value of the outlet, the magnitude of the discharge water makes the company's difficulties to deal with it, because there has been no water discharge measurements in detail. Water discharge measurements on the system is difficult because the aquifer is secondary to the absence of a map distribution structure, therefore the measurement was done manually. And now CV. Tahiti Coal haven’t settling pond as a water quality control places accordingly has not met the requirements by the KEPMEN Mining and Energy No: 1211.K/008/M.PE/1995 chapter 9 paragraph 1 and paragraph 2. This type of research belongs to the type of applied research. As the result of data processing discharge ground water totally 5,092 m3/minute. The total of pumps needed to re-draft installation pump Tsurumi pump   Hs(Z)3,75S-51 12 units company provided appropriate and required the addition of pump 3 units pumps Tsurumi LH637-HDPE pipes in diameter of  6 inch. Sump 1 is rectangular with dimensions length 2 m, width 1 m, and a depth of 2 m. Sump 2 is a  trapezium with dimensions length 10.12 m, width 6.6 m and a depth of 3 m.  settling pond is planned 3 compartments, 2 partitions, the depth of the pond 4 m with a capacity of each compartment of 254 m3 and the capacity of entire 761.18 m3.Keywords:  Pump, Instalation Pump, Head Losess, Sump, Settling Pond